THE EDUCATIONAL IDEOLOGY OF INDONESIAN AND MALAYSIAN PESANTRENS: A STUDY OF AL MUNAWIR AND PASIR TUMBOH - Ahmad Rodli; Imam Machali; Zainal Arifin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
The research mainly focuses on the comparative analysis towards the ideology and epistemology applied in Al Munawir Krapyak, Yogyakarta, Indonesia and Pasir Tumboh, Kelantan, Malaysia; both are pesantrens or traditional education institution-also called islamic boarding school. The study denotes that the curriculum utilized in al munawir pesantren is integrated Islam and science. While Pasir Tumboh employs the classical curriculum called kitab Jawi (Melayu). The epistemological base of curriculum of Al Munawir is Burhani-Irfani (demonstrative-gnostic) which in turn leads to transcendental contextual mindsets. It is rational religious ideology that modifies the methodology of Ahlussunnah Waljamaah emphasizing moderate and open-minded islamic teaching. On the other hand, the epistemological base of curriculum of Pasir Tumboh is Bayani-Irfani (explanative-gnostic) producing religious conservative ideology which is textual-trancendental, pseudo-exclusive and normative in observing the methods of ahlussunnah waljamaah.